A Runoff Prediction Equation for Small Watersheds for Use in Watershed Planning in the Ambala Siwaliks - Erasmus, I. I.; Bansal, R. C. (Indian Forester, 1965)
Runoff data for six different sized experimental watersheds at the Soil Conservation Research Station, Chandigarh, has been correlated with rainfall intensity and area. A runoff prediction equation has been derived for application in small watersheds in the Ambala Siwaliks.